Antibacterial Activities Of Papaya Seed (Carica papaya L.) Ethanol Extract With MAE And UAE Extraction Methods Towards Staphylococcus aureus - Hartanti, Fini; Hidayati, Devi Nisa (Media Farmasi: Jurnal Ilmu Farmasi, 2023)
Ethanol extract of papaya seeds produced by the maceration method has been shown to have antibacterial activity against S. aureus, P. aeruginous, S. thypi, and E. coli. This study aims to compare the antibacterial activity of the ethanol extract of papaya seeds obtained using the Microwave Assisted Extraction (MAE) and Ultrasound-Assisted Extraction (UAE) extraction methods on the growth of Staphylococcus aureus bacteria.Papaya seed powder was extracted using MAE and UAE extraction methods using 70% ethanol as a solvent in concentrations of 20%, 40%, 60%, and 80%. DMSO was used as negative control and chloramphenicol 30 g/disk as a positive control. The antibacterial activity test method used the disk diffusion method. The parameter observed was DDH (Diameter of Inhibitory Area) which was statistically analyzed using Two Way Anova at a 95% confidence level.The results showed that the ethanol extract of papaya seeds produced from the MAE and UAE extraction methods had antibacterial activity against Staphylococcus aureus in all concentration series. The statistical test showed a significant difference (p<0.05) in antibacterial activity against Staphylococcus aureus extracts obtained from two extraction methods: MAE and UAE. UAE method is recommended use.